2012
DOI: 10.1590/s0100-83582012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de nutrientes e matéria seca na parte aérea de dois cultivares de soja RR sob efeito de formulações de glyphosate

Abstract: Palavras-chave: Glycine max, herbicida, inibidores da EPSPs, nutrição, seletividade.ABSTRACT -The study of selectivity and secondary effects of herbicides on crops is extremely important to successful agriculture. This research aimed to evaluate the effect of glyphosate formulations on nutrient accumulation and dry matter production on the shoot of two glyphosateresistant (GR) soybean cultivars. The assay was carried out in a greenhouse and arranged in a randomized complete block design, replicated six times. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
1
5
0
1
Order By: Relevance
“…These results are directly related to those discussed by several authors, probably because they are connected or arise from potential injury, or even from the harmful effects of glyphosate and its metabolites, as found in the literature Zablotowicz & Reddy, 2004;Santos et al, 2007;Zablotowicz & Reddy, 2007;Zobiole et al, 2010a,b,c;Albrecht, et al, 2011a,b;Albrecht et al, 2012a,b;Cavalieri et al, 2012).…”
Section: Resultssupporting
confidence: 81%
“…These results are directly related to those discussed by several authors, probably because they are connected or arise from potential injury, or even from the harmful effects of glyphosate and its metabolites, as found in the literature Zablotowicz & Reddy, 2004;Santos et al, 2007;Zablotowicz & Reddy, 2007;Zobiole et al, 2010a,b,c;Albrecht, et al, 2011a,b;Albrecht et al, 2012a,b;Cavalieri et al, 2012).…”
Section: Resultssupporting
confidence: 81%
“…After each harvest, 5 plants of each plot were separated into branches, leaves and pods for weighing and determining the wet mass of each component (WMB; WML; WMP); then the plants of the plot were ground to obtain the ground natural matter (GNM). After this, the material was dried in a forced air circulation oven at 60°C to determine the dry weight of branches, leaves and pods and the dry weight of the composite sample (DWB; DWL; DWP; DWCS) according to the methodologies used by Neumann et al (2011); Calvo, Simoneti, and Brancalião (2010) and Cavalieri, Velini, Silva, São José, and Andrade (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the impacts of GBHs on plants and other organisms may differ substantially from those of glyphosate and its salts, commonly the isopropylamine salt [ 17 19 ]. In turn, different GBH formulations have been shown to exert different effects on crops [ 20 ]. We endeavour throughout this review to cite the specific formulations used in experiments (e.g.…”
Section: Properties Of Glyphosatementioning
confidence: 99%
“…However, a small number of studies have reported significant disruptions to GR crop nutrition, as well as declines in plant biomass production, chlorophyll content and photosynthetic rate, associated with GBH treatments at the recommended herbicidal dosage to GR crops [ 20 , 79 , 92 – 96 ]. These studies and their main findings are summarised as follows.…”
Section: The Influence Of Gbhs On Crops’ Disease Resistancementioning
confidence: 99%